The Effect of Vitamin D Supplementation on Skeletal Muscle in the mdx Mouse Model of Duchenne Muscular Dystrophy - Danielle A. Debruin; Nicola Andreacchio; Erik D. Hanson; Cara A. Timpani; Emma Rybalka; Alan Hayes (MDPI AG, 2019)
Vitamin D (VitD) has shown to be beneficial in reversing muscle weakness and atrophy associated with VitD deficiency. Duchenne muscular dystrophy is characterized by worsening muscle weakness and muscle atrophy, with VitD deficiency commonly observed. This study aimed to investigate the effect of VitD supplementation on dystrophic skeletal muscle. Eight-week old female control (C57BL/10; n = 29) and dystrophic (C57BL/mdx; n = 23) mice were randomly supplemented with one of three VitD enriched diets (1000, 8000 & 20,000 IU/kg chow). Following a four-week feeding period, the extensor digitorum longus (EDL) and soleus muscles contractile and fatigue properties were tested ex vivo, followed by histological analysis. As expected, mdx muscles displayed higher mass yet lower specific forces and a rightward shift in their force frequency relationship consistent with dystrophic pathology. There was a trend for mdx muscle mass to be larger following the 20,000 IU/kg diet, but this did not result in improved force production. Fiber area in the EDL was larger in mdx compared to controls, and there were higher amounts of damage in both muscles, with VitD supplementation having no effect. Four weeks of VitD supplementation did not appear to have any impact upon dystrophic skeletal muscle pathology at this age.